Study some Electrical Properties of Cu2ZnSnS4 Thin Films Prepared by Pulse Laser Deposition (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background Pulses increased the thin-film sample preparation was carried out via a laser ablation method.     5 tons of pressure which were used to compress powdered (CZTS) pellet form. Utilizing a Neodymium-YAG laser with a range of 700mJ laser energy, and the plasma plume was created at a pressure of 10-5mbar utilizing at a frequency of 6Hz. Electrical Properties including Hall effect and electrical conductivity were investigated. According to Hall measurements, the films prepared were p-type at 200 pulses and changed to n-type as the number of pulses increased. They also had two activation energies (Ea1 ,Ea2). The conductivity was shown to increase as the number of pulses increased. Materials and MethodA Neodymium-YAG laser with a range of 700mJ laser energy, and the plasma plume of            10-5mbar were utilizing number of pulses at a frequency of 6Hz. The Hall effect and electrical conductivity were investigated.ResultsHall effect and D.C were studied. According to the findings, the prepared films were p-type at 200 pulses and changed to n-type as the number of pulses increase. They also had two activation energies (Ea1 and Ea2).The electrical conductivity was shown to increase as the number of  pulses. ConclusionsTwo activation energies ( Ea1 , Ea2). Hopping method for moving the carriers between levels inside the energy gap and the thermal stimulation method for moving between other levels. The carrier type of CZTS compound films change from p-type to n-type as the number laser pulses increase.